التفكير التأملي وعلاقته بالالتزام الديني لدى طلبة جامعة مؤتة - Khaled Muflih Dweirj Almarayeh; Fuad Talafeh; Mikail Ibrahim; Sulaiman Ismail (USIM Press, 2024)
Al-Azkiyaa Vol:. 2 No: 2 (page: 155–173)